Efeitos farmacológicos do telocinobufagin, um bufadienolídeo oriundo das glândulas parotóides do Bufo paracnemis : estudo comparativo com o anestésico local bupivacaína - Patrocínio, Manoel Cláudio Azevedo (2004)
The pharmacological effects of telocinobufagin (TCB), a bufadienolide extracted from Bufo paracnemis parotoid glands by HPLC, were compared to that induced by bupivacaine (BUPI). On guinea-pig isolated ileum, TCB (10-8 to 10-4 M) inhibited both, the electrical field stimulation (EFS)-induced contraction (with a value of 0.9 ± 0.9 % of the control response at 6x10-4 M), and the contractions elicited by ACh, in a concentration-dependent manner. BUPI (10-7 to 10-3 M) also inhibited both, the EFS- and the ACh-induced contractions on guinea-pig isolated ileum, in a concentration-dependent manner. On rat isolated sciatic nerve, TCB (1 mM) reduced the compound action potential (CAP) peak-to-peak amplitude (PPA) to 64.9±7.2 % and 12.9±4.4 % of the control amplitude after 15 min and 30 min, respectively; withdrawal of telocinobufagin reversed to 83.2±17.5% after 45 min. TCB reduced the CAP conduction velocity (CV) to 15.0±15.0 % of the control after 30 min; wash reversed to 78.7±7.2 % of the control. BUPI (1 mM) inhibited the CAP PPA to 46.7±14,4 % and 11.8.±6.5 % of the control after 15 min and 30 min, respectively; it recovered partially to 29.7±8.3 % after 45 min of wash. BUPI inhibited the CAP CV to 17.4±11.2 % of the control after 30 min; it recovered partially to 44.8±14.5 % after 45 min of wash. On rat isolated atrium, TCB (10-6 to 10-4 M) did not alter the spontaneous inotropism, which was abolished by BUPI. Thus, TCB showed a reversible local anesthetic action, similar to BUPI, however, without cardiac toxicity in vitro. This study shows perspectives to research of new molecules for local anesthetic activity with therapeutic interest.